2022
DOI: 10.1956/jge.v18i1.634
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Foreign Direct Investment on Poverty Alleviation in East Africa Countries

Abstract: Foreign Direct Investment (FDI) is crucial to support economic development for developed and developing countries. The aim of this paper is to examine the effect of Foreign Direct Investment (FDI) on poverty alleviation in East Africa Countries. The study adopted a time series data research design where by secondary data were used. The population applied on the financial records from 1987/88 - 2017/18 financial years (Annual Data). The sample size of the study was 31 annual observations. Tanzania was purposive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…on the other hand, Fauzel, Seetanah, and Sannassee (2015) adopted dynamic Panel vector error correction model that discovered a significant negative association between the factors. On the contrary, FDI inflow helped in poverty reduction in Nepal and Sri Lanka while increasing poverty in Pakistan and Bangladesh (Chindengwike, 2022a;Mahmood & Chaudhary, 2012). Lazreg and Zouari (2018) have also proved through unit root test of co-integration, the model error correction of FMOLS and Granger causality that FDI and poverty have negative correlation to each other in Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…on the other hand, Fauzel, Seetanah, and Sannassee (2015) adopted dynamic Panel vector error correction model that discovered a significant negative association between the factors. On the contrary, FDI inflow helped in poverty reduction in Nepal and Sri Lanka while increasing poverty in Pakistan and Bangladesh (Chindengwike, 2022a;Mahmood & Chaudhary, 2012). Lazreg and Zouari (2018) have also proved through unit root test of co-integration, the model error correction of FMOLS and Granger causality that FDI and poverty have negative correlation to each other in Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lazreg and Zouari (2018) have also proved through unit root test of co-integration, the model error correction of FMOLS and Granger causality that FDI and poverty have negative correlation to each other in Pakistan. (Chindengwike, 2022a) disclosed that FDI was in a positive relation to the poverty alleviation among the developing and underdeveloped countries using time series data analysis from 1987-2017 for Tanzania. On the other hand, the GINI index revealed that FDI tends to increase poverty.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study applied the ARDL model and found that FDI inflows, TOP and GDP considerably reduce the level of poverty both in the short and long run. Likewise, Chindengweike (2022) examined the effect of FDI on poverty alleviation for a panel of 31 East African countries from 1987 to 2018 and used a multiple linear regression estimator. The overall empirical result revealed that FDI significantly decreased poverty over time.…”
Section: Theoretical Review and Empirical Reviewmentioning
confidence: 99%